Formulation and Evaluation of Cilnidipine Loaded Nanocapsules Suspension for Hypertension Management - Indira Muzib, Y.; N, Roja; Ambedkar, Y. R. (European Journal of Applied Sciences, 2025)
Hypertension is one of the major causes of cardiovascular diseases, necessitating effective and sustained drug delivery systems for optimal treatment. Cilnidipine, is a dual calcium channel blocker, has demonstrated significant efficacy in managing hypertension. Due to poor solubility and bioavailability its therapeutic potential is often limited.The main objective of this study was to develop, characterize, and evaluate cilnidipine-loaded nano capsule suspensions as an advanced drug delivery system for the treatment of hypertension. Cilnidipine nanocapsules(CN) were prepared using a solvent evaporation method, and their physicochemical properties, such as particle size, zeta potential, drug loading efficiency, and morphology, were systematically analysed. Developed 8 formulations (CN1-CN8) with various ratios 2 different polymers. The optimized cilnidipine nanocapsule suspension compatibility studies conducted by using Fourier transform infrared spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) that confirmed the absence of any interactions between drug and excipients showcasing uniformly distributed particles.CN8 formulation was showing better results among all remaining formulation. The stability studies confirmed the nanocapsules’ suitability for long-term storage, making them an ideal candidate for clinical use.Cilnidipine-loaded nanocapsule suspensions offer a promising strategy for improving the management of hypertension by providing controlled release, reduced side effects, and enhanced therapeutic efficacy.